PEMANFAATAN BIOAKTIVATOR BONGGOL PISANG DAN PENAMBAHAN BIOCHAR ARANG SEKAM PADI TERHADAP PERTUMBUHAN TANAMAN KEDELAI (Glycine max L. Merril) var. anjasmoro - Chisa Amanda, Adelia; Ajiningrum, Purity Sabila (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2023)
The provision of bioactivators is one of the cultivation techniques that can increase soybean production. Bioactivators that can be used are banana weevil with the addition of rice husk charcoal biochar. This study aims to determine the effect of banana weevil bioactivator with the addition of rice husk charcoal biochar with 2 controls, namely 0% negative control and positive control (em4 bioactivator) and 3 treatments namely P1 (10%), P2 (15%), P3 (20 %) in increasing the growth of soybean plants and to determine the optimal concentration of each treatment given. This study used a completely randomized design (CRD) with 5 treatments and 5 replications. The research data were then analyzed by using the ANOVA test followed by the LSD test and Duncan's test. The results showed that giving banana weevil bioactivators with the addition of rice husk charcoal Biochar had a significant effect (P <0.05) on the growth (plant height and number of leaves) of soybean plants with the optimal concentration in the P3 treatment with a concentration of 20%.   Keywords: bioactivator, biochar, soybean, banana weevil, rice husk